Determinants of Obstetric Ultrasound Utilization Among Pregnant Women in Efforts to Prevent the Infant Mortality Rate in Tulang Bawang Regency - Afdinda Firtanti; Endang Budiati; Dewi Rahayu; Dian Utama Pratiwi Putri (Health Dynamics, 2026)
Background: Low utilization of ultrasonography (USG) examinations among pregnant women, at only 16.1% during the first antenatal care (ANC) visit and 18.7% during the last ANC visit, may hinder the early detection of pregnancy complications and contribute to the high infant mortality rate (IMR), which reached 34 cases in 2024 in Tulang Bawang Regency. This study aimed to analyze the determinants of USG examination utilization among pregnant women in Tulang Bawang Regency in 2025. Methods: This quantitative analytic study employed a cross-sectional design. From a population of 2,694 pregnant women in Tulang Bawang Regency in 2025, a sample of 267 respondents was selected using stratified random sampling from six primary health centers. Data were collected using questionnaires and secondary data sources. Data analysis included univariate, bivariate (Chi-square), and multivariate analyses using multiple logistic regression. Results: Of the 267 respondents, 141 (52.8%) adhered to ultrasound examinations. Knowledge (p=0.000), attitude (p=0.008), age (p=0.000), service availability (p=0.008), accessibility (p=0.000), and perception (p=0.013) were significantly associated with ultrasound examination adherence, whereas pregnancy risk status was not significantly associated (p=0.643). Age was identified as the dominant factor influencing ultrasound examination adherence (p=0.001; OR=3.660; 95% CI: 1.751–7.650). Conclusions: Ultrasound utilization among pregnant women was primarily influenced by age, accessibility, and knowledge. To improve ultrasound utilization as an innovation to strengthen ANC services, we recommend prioritizing screening among pregnant women aged <20 and >35 years, providing structured ultrasound education, implementing written scheduling systems, tiered reminders, and active follow-up for missed appointments. These efforts should be supported by flexible service hours and improved accessibility through scheduled transportation and mobile ultrasound services, subject to resource availability.